# Find the inverse of f(x)=5tan(3x+4)

## Expert Answers info

Sarah Goodale | Certified Educator

calendarEducator since 2018

write614 answers

starTop subjects are Literature, History, and Social Sciences

The first step in finding an inverse function is to write the function in “y equals” notation, as it will allow us simply to switch the variables and solve for us once again as follows:

Let y=5*tan(3x+4)
Now switch x and y:
x=5*tan(3y+4)
Now solve for y algebraically using the conventional order of operations:
x/5=tan(3x+4)
Now take the...

(The entire section contains 2 answers and 206 words.)

### Unlock This Answer Now

check Approved by eNotes Editorial

## Related Questions

Rylan Hills | Certified Educator

calendarEducator since 2010

write12,544 answers

starTop subjects are Math, Science, and Business

check Approved by eNotes Editorial

giorgiana1976 | Student

Let f(x) = y.

y = 5tan(3x+4)

First, we'll interchange x and y:

x = 5tan(3y+4)

We'll divide by 5:

x/5 = tan(3y+4)

3y + 4 = arctan (x/5)

We'll subtract 4 both sides:

3y = arctan (x/5) - 4

We'll divide by 3:

y = [arctan (x/5) - 4]/3

The requested inverse function is: f^-1(x) = [arctan (x/5) - 4]/3

check Approved by eNotes Editorial